The Influence of The Weight of N,N’-Methylene-bis-Acrylamide as Crosslinker on The Ability of Chitosan-Graft-Poly (Acrylic Acid) Superabsorbent to Water Retention in Sandy Soil - Amin Yulianto; Jayanudin; Heri Heriyanto; Dimas Prasetyo (Jurnal Bahan Alam Terbarukan, 2024)
Enhancing the agricultural productivity of sandy soil can be achieved by incorporating a superabsorbent material that serves dual purposes: improving water retention and gradually releasing fertilizer nutrients. The objective of this study is to determine the influence of the weight of N,N’-methylene-bis-acrylamide (MBA) as a crosslinker in chitosan-graft-poly(acrylic acid) superabsorbent on water holding and water retention in sandy soil. The superabsorbent was prepared by mixing a chitosan solution with ammonium persulfate as a catalyst and acrylic acid, which had been neutralized with KOH. Subsequently, the mixture was cross-linked using MBA. The resulting superabsorbent indicated that an increase in the weight of MBA decreased the swelling ratio and increased water retention due to a denser network structure. The water holding capacity for superabsorbent prepared with all MBA weights was nearly the same. The highest swelling ratio and water retention were 167.552 g/g and contained 7.6% water on day 7 for the superabsorbent crosslinked with 0.015 g of MBA.